2017
DOI: 10.1017/s1047951117001949
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular adaptation to extrauterine life after intrauterine growth restriction

Abstract: Neonates with history of intrauterine growth restriction showed cardiac remodelling and signs of systolic and diastolic dysfunction. Overall, there was a significant tendency to worse cardiac function results in the right heart. The adaptation to extrauterine life occurred with more globular hearts, higher stroke volumes but a similar heart rate compared to adequate-for-gestational-age neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
(78 reference statements)
1
11
0
1
Order By: Relevance
“…Studies in neonates with FGR have also found the RV and LV transverse widths to be increased compared to controls. 2,6 Hobbins et al 13 measured the end-diastolic area of the RV and LV and found no increase in areas in fetuses with an EFW below the 10th centile with a normal UA PI but reported a significant number of fetuses with decreased end-diastolic areas for both ventricles when the UA PI was abnormal. 13 Of interest, decreased LV and RV areas and 24-segment transverse widths were only identified in neonatal survivors in our study.…”
Section: Previous Studies Evaluating the 4cv Size And Shapementioning
confidence: 99%
See 3 more Smart Citations
“…Studies in neonates with FGR have also found the RV and LV transverse widths to be increased compared to controls. 2,6 Hobbins et al 13 measured the end-diastolic area of the RV and LV and found no increase in areas in fetuses with an EFW below the 10th centile with a normal UA PI but reported a significant number of fetuses with decreased end-diastolic areas for both ventricles when the UA PI was abnormal. 13 Of interest, decreased LV and RV areas and 24-segment transverse widths were only identified in neonatal survivors in our study.…”
Section: Previous Studies Evaluating the 4cv Size And Shapementioning
confidence: 99%
“…The results from the z score computations were classified as above the 95th centile ( z > 1.65) or below 5th centile ( z < −1.65), depending on the measurement. Once the z scores were computed for each of the above measurements, the numbers of fetuses with abnormal z score values were compared to the expected numbers of abnormal values for the 5th and 95th centiles from control populations by the χ 2 analysis or the Fisher exact test (NCSS version 19; NCSS, Kaysville, UT) 8–11,16,25 . In addition, z score values for the above measurements were compared between the two groups by the Student t test if the variables were normally distributed or the Mann–Whitney U test if the measurements were not normally distributed.…”
Section: Z Score = (Individual Measured Cardiac Value Study Group – Meancontrol Group)/sdcontrol Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…■ Keywords: newborn; intrauterine growth retardation; neuron-specific enolase; brain-derived neurotrophic factor. недостаточности нарушается генетическая программа развития всех функциональных систем орга низма плода, что затрудняет постнатальную адаптацию и программирует риск небла гоприятных последствий [5][6][7][8][9]. При этом значительные структурно-функциональные изменения на клеточном уровне способствуют возникновению глубоких нарушений гомеостаза мозга, продукции и метаболизма нейромедиаторов, нейромодуляторов и нейрогормонов [10][11][12][13].…”
unclassified